2016
DOI: 10.1017/cnj.2016.11
|View full text |Cite
|
Sign up to set email alerts
|

St’át'imcets intonation contours: a preliminary study

Abstract: Acoustic research on the prosody and intonation of Northwest Coast languages has until recently been under-researched. This paper joins the growing body of research on the subject and reports on the results of the first study of intonation in St’át'imcets (Lillooet Salish; Northern Interior Salish). It tests the generalization proposed by Davis (2007) that information structure is not correlated with prosody in Salish languages by comparing the intonation contours of declaratives and yes/no questions. Specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The reliability of pausing as a correlate to prosodic, syntactic and discourse units has been debated in commonly-studied languages (outlined, for instance, in [1]). Preliminary research in Nxaʔamxčín (Interior Salish) [2] has shown that pausing could be a more reliable acoustic correlate of discourse structure than pitch, in line with previous research indicating that Salish languages do not exhibit a strong reliance on pitch to mark information structure [3][4][5][6].…”
Section: Introductionmentioning
confidence: 53%
“…The reliability of pausing as a correlate to prosodic, syntactic and discourse units has been debated in commonly-studied languages (outlined, for instance, in [1]). Preliminary research in Nxaʔamxčín (Interior Salish) [2] has shown that pausing could be a more reliable acoustic correlate of discourse structure than pitch, in line with previous research indicating that Salish languages do not exhibit a strong reliance on pitch to mark information structure [3][4][5][6].…”
Section: Introductionmentioning
confidence: 53%